Prion Diseases and the Gastrointestinal Tract - Gwynivere A Davies; Adam R Bryant; John D Reynolds; Frank R Jirik; Keith A Sharkey (Canadian Journal of Gastroenterology)
The gastrointestinal (GI) tract plays a central role in the pathogenesis of transmissible spongiform encephalopathies. These are human and animal diseases that include bovine spongiform encephalopathy, scrapie and Creutzfeldt-Jakob disease. They are uniformly fatal neurological diseases, which are characterized by ataxia and vacuolation in the central nervous system. Alhough they are known to be caused by the conversion of normal cellular prion protein to its infectious conformational isoform (PrPsc) the process by which this isoform is propagated and transported to the brain remains poorly understood. M cells, dendritic cells and possibly enteroendocrine cells are important in the movement of infectious prions across the GI epithelium. From there, PrPsc propagation requires B lymphocytes, dendritic cells and follicular dendritic cells of Peyer’s patches. The early accumulation of the disease-causing agent in the plexuses of the enteric nervous system supports the contention that the autonomic nervous system is important in disease transmission. This is further supported by the presence of PrPsc in the ganglia of the parasympathetic and sympathetic nerves that innervate the GI tract. Additionally, the lymphoreticular system has been implicated as the route of transmission from the gut to the brain. Although normal cellular prion protein is found in the enteric nervous system, its role has not been characterized. Further research is required to understand how the cellular components of the gut wall interact to propagate and transmit infectious prions to develop potential therapies that may prevent the progression of transmissible spongiform encephalopathies.